„Mogę powiedzieć [...], że jednak – jestem”. Czesława Miłosza sposoby odkrywania siebie - Telicki, Marcin (Poznańskie Studia Polonistyczne. Seria Literacka, 2012)
The article discusses the plausibility of Joanna Zach’s concept described as the “poetic of confession”. “Self discovery” is, for Miłosz, related to Romantic and early-Modernist sources of creative expression, and to poetry as a specific confession of faith. This, in turn, assumes an unending tension between biography, immersed in concrete reality, and its textual representation (the truth of life is confronted with the truth of poetry). What follows is that for Miłosz the key category is experience, suspended between history and the present, and between reality and its textual transformation.